Associations between thyroid function, thyroid hormone sensitivity indices, and frailty: Insights from a large cross-sectional study - Yusheng Zhang; Daowen Zhang; Chenwen Yuan; Yiming Wang; Hao Zhu; Yu Duan (Experimental Gerontology)
Background: This research aims to assess the relationships of thyroid hormones and thyroid hormone sensitivity with frailty among adults in the United States. Methods: This study assessed frailty through a 49-item Frailty Index based on the inclusion of 4011 participants from the National Health and Nutrition Examination Survey (NHANES; 2007–2012). Furthermore, this study employed logistic regression, sensitivity analysis, subgroup analysis, restricted cubic splines (RCS), and threshold effect analysis to compare and analyze relation between frailty and thyroid hormone levels as well as sensitivity indices across all ages, particularly in the middle-aged and elderly populations. Results: A total of 4011 participants were included, with 63.65 % classified as frail based on the Frailty Index (FI). Frail individuals had higher thyroid-stimulating hormone (TSH), free thyroxine (FT4), and total thyroxine (TT4), but lower free triiodothyronine (FT3) and total triiodothyronine (TT3) levels. Thyroid hormone sensitivity indices revealed disparities in FT3/FT4 and thyrotropin thyroxine resistance index (TT4RI). Logistic regression models indicated a negative association between FT3, TT3 and frailty, even after adjusting for all covariates (OR = 0.58, 95 % CI: 0.41–0.84 for FT3; OR = 0.99, 95 % CI: 0.99–0.99 for TT3). Sensitivity analysis increases the robustness of the correlation. Subgroup analyses showed that FT3 had a statistically significant inverse correlation in younger (20–44) and middle-aged (45–59) groups (P = 0.042 and P = 0.034). While, TT3 showed a negative association with frailty in younger (20–44) and older (60+) groups (P = 0.037 and P = 0.028). In RCS analysis, significant nonlinear relationships were observed between frailty and all thyroid hormones as well as thyroid hormone sensitivity indices except for TSH and TSHI in the older age group. In the middle-aged group, significant nonlinear relationships were also found between frailty and FT4, FT3/FT4, and Thyroid Feedback Quantile-based Index (TFQI(FT4)) (P nonlinear <0.05). Threshold effect analysis revealed consistent inflection points for FT3 (K = 3.5) across age groups, while FT4 and TFQI(FT4) had different inflection points in middle-aged and older individuals. Conclusion: Thyroid hormone changes exhibit intimate association with frailty development, highlighting the importance of monitoring thyroid function and thyroid sensitivity indices for both early identification and intervention.